0383 Clinical Impact of Pitolisant on Excessive Daytime Sleepiness and Cataplexy in Adults With High Burden of Narcolepsy Symptoms. (25th May 2022) - Meskill, Gerard; Davis, Craig; Zarycranski, Donna; Doliba, Markiyan; Schwartz, Jean-Charles; Dayno, Jeffrey
Abstract: Introduction: This post hoc analysis evaluated the clinical impact of pitolisant for the reduction of excessive daytime sleepiness (EDS) and cataplexy in adults with a high burden of narcolepsy symptoms. When evaluating results of randomized, placebo-controlled trials, the clinical impact of a treatment can be assessed using effect size metrics that include Cohen's d (the standardized mean difference of an effect) and number needed to treat (NNT; number of patients that need to be treated to achieve a specific outcome for one person). Methods: Data were pooled from 2 randomized, placebo-controlled, 7- and 8-week studies of pitolisant (individually titrated; potential maximum dose, 35.6 mg/day) in adults with narcolepsy. Analyses included 3 independent patient subgroups with high symptom burden: (1) baseline score of ≥16 on the Epworth Sleepiness Scale (ESS), (2) sleep latency of ≤8 minutes on the Maintenance of Wakefulness Test (MWT), and (3) ≥15 cataplexy attacks per week. Efficacy measures included the ESS, MWT, weekly rate of cataplexy (WRC), and Clinical Global Impression of Change (CGI-C). Cohen's d was derived from the least-squares mean difference between treatment groups (pitolisant vs placebo), and NNTs were calculated from response rates. Missing values were imputed using a last observation carried forward approach. Results: The high-burden populations included 118 patients for the ESS subgroup (pitolisant, n=60; placebo, n=58), 105 for MWT (pitolisant, n=59; placebo, n=46), and 31 for cataplexy (pitolisant, n=20; placebo, n=11). Cohen's d effect size values for pitolisant versus placebo were 0.80 for ESS, 0.31 for MWT, and 1.31 for WRC. NNTs for pitolisant were 3 for ESS score reduction (≥3-point decrease from baseline or final score ≤10) in the ESS subgroup and 2 for WRC reduction (≥50% decrease from baseline) in the cataplexy subgroup. For the CGI-C for EDS ("much" or "very much" improved), NNT was 5 in the ESS subgroup and 4 in the MWT subgroup; for the CGI-C for cataplexy, NNT was 3 in the cataplexy subgroup. Conclusion: The results of this analysis demonstrate the robust efficacy of pitolisant for the reduction of both EDS and cataplexy in patients with severe narcolepsy symptom burden. Support (If Any): Bioprojet Pharma and Harmony Biosciences, LLC.